2020
DOI: 10.3390/catal10101194
|View full text |Cite
|
Sign up to set email alerts
|

Vis-Responsive Copper-Modified Titania for Decomposition of Organic Compounds and Microorganisms

Abstract: Seven commercial titania (titanium(IV) oxide; TiO2) powders with different structural properties and crystalline compositions (anatase/rutile) were modified with copper by two variants of a photodeposition method, i.e., methanol dehydrogenation and water oxidation. The samples were characterized by diffuse reflectance spectroscopy (DRS), X-ray powder diffraction (XRD), scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS) and X-ray photoelectron spectroscopy (XPS). Although zero-valent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 122 publications
2
13
0
Order By: Relevance
“…Here, the zero-valent form of gold is the most predominant, reaching 92%. In the case of copper, only its oxidized forms could be detected, i.e., Cu + (932.16 eV [68]; 58%) and Cu 2+ (932.28 eV [68]; 42%), confirming the instability of zero-valent copper under ambient conditions [69][70][71]. As expected, palladium and platinum exist mainly in the zero-valent form, reaching 80% and 79%, respectively, making up the minority of the oxidized forms of metals (probably PdO [72] and Pt(δ+) [68]).…”
Section: Characterization Of Samplesmentioning
confidence: 85%
“…Here, the zero-valent form of gold is the most predominant, reaching 92%. In the case of copper, only its oxidized forms could be detected, i.e., Cu + (932.16 eV [68]; 58%) and Cu 2+ (932.28 eV [68]; 42%), confirming the instability of zero-valent copper under ambient conditions [69][70][71]. As expected, palladium and platinum exist mainly in the zero-valent form, reaching 80% and 79%, respectively, making up the minority of the oxidized forms of metals (probably PdO [72] and Pt(δ+) [68]).…”
Section: Characterization Of Samplesmentioning
confidence: 85%
“…It was shown that copper is not genotoxic and does not cause DNA mutations or affect the enzymatic reactions inside the cells. On the other hand, this concept raises a lot of controversy, particularly with regard to photocatalytic materials (e.g., CuO 2 , CuxO@TiO 2 ) that present their antimicrobial effect when exposed to light [ 9 , 27 , 33 , 38 ]. It is possible that extended ROS generation by induced Fenton-like reactions could lead to an imbalance between the production and accumulation of reactive oxygen species (ROS) in cells (defined as oxidative stress), cell respiration arrest, or even DNA breakdowns.…”
Section: Discussionmentioning
confidence: 99%
“…Ag, Cu, and Au nanoparticles have also been used as germ-destroying agents [ 6 ]. They were investigated before the ongoing pandemic, but over the past two years there has been growing interest in this topic [ 7 , 8 , 9 ]. The scientific rationales for addressing this issue are: (i) metals can efficiently prevent virus and bacteria transmission [ 10 ]; (ii) bacterial/SARS-CoV-2 coinfections and secondary bacterial “super-infection” after SARS-CoV-2 play a significant role during COVID-19 infection [ 11 , 12 ]; (iii) the SARS-CoV-2 pandemic is superimposed on the ongoing pandemic of antibiotic-resistant bacteria (ARB); (iv) the common use of sanitizers and antibacterial agents as personal measures can enhance the transmission of antibiotic-resistance genes (ARG) [ 13 ]; and (v) microbial resistance to metal NPs is almost impossible [ 6 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zero-valent copper has been proposed as a promising co-catalytic material for photocatalysis, since copper has similar electronic properties to silver and gold, and is much cheaper. However, copper is easily oxidized when kept under ambient conditions (as discussed above) [42,43,49,50]. Therefore, formed, less active copper species (though Zero-valent copper has been proposed as a promising co-catalytic material for photocatalysis, since copper has similar electronic properties to silver and gold, and is much cheaper.…”
Section: Zero-dimension (0d) Photocatalystsmentioning
confidence: 99%
“…Therefore, formed, less active copper species (though Zero-valent copper has been proposed as a promising co-catalytic material for photocatalysis, since copper has similar electronic properties to silver and gold, and is much cheaper. However, copper is easily oxidized when kept under ambient conditions (as discussed above) [42,43,49,50]. Therefore, formed, less active copper species (though probably re-reduced under reductive conditions during hydrogen generation [43]) could seriously limit the practical application of copper-based photocatalysts [51].…”
Section: Zero-dimension (0d) Photocatalystsmentioning
confidence: 99%